2007
DOI: 10.1111/j.1651-2227.2007.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐sensitivity C‐reactive protein in children at risk for coronary artery disease

Abstract: Serum hs-CRP level is a useful marker in screening the children who are under the risk of CHD in adulthood. Early identification of the children with risk factors and intervention for obesity, harmful habits and life style in childhood might decrease the incidence of coronary heart disease in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
4
18
2
3
Order By: Relevance
“…Previous studies have shown similar results in young overweight and obese individuals [7,8,[11][12][13][14]18]. However, the values of hs-CRP obtained in our study are higher as compared to some previous observations [11].…”
Section: Correlation Between Hscrp and Other Parameterscontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have shown similar results in young overweight and obese individuals [7,8,[11][12][13][14]18]. However, the values of hs-CRP obtained in our study are higher as compared to some previous observations [11].…”
Section: Correlation Between Hscrp and Other Parameterscontrasting
confidence: 56%
“…High CRP levels also correlate well with other parameters of MS [10]. Majority of the previous studies showing raised CRP levels in obese children are from the developed countries [4][5][6][7][8][9][11][12][13][14]. The need to generate data from the developing countries is even more in view of the recent observations and recommendations for diagnosis of obesity and MS for Asian Indians [15].…”
Section: Introductionmentioning
confidence: 99%
“…CRP, C3, C4, adiponectin and leptin were determined in serum, fibrinogen was determined in plasma and ESR was determined in whole blood. The existing literature shows that all the biomarkers analyzed in this study have been increasingly explored in studies involving children or adolescents [24][25][26][27] , suggesting that they are a valid choice for this age group.…”
Section: Biochemical Assessmentmentioning
confidence: 99%
“…Later studies have shown high values of hs-CRP among obese children and adolescents, indicating that in early stages there already exists a certain level of inflammation in relation to the non-obese population (5)(6)(7)(8). However, not many data are available that guarantee its utility as a marker of cardiovascular risk and diabetes in childhood (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, not many data are available that guarantee its utility as a marker of cardiovascular risk and diabetes in childhood (7,8). Therefore, our intention is to study the levels of hs-CRP in obese children and adolescents with and without metabolic syndrome to evaluate the utility of this parameter as a method of early diagnosis of cardiovascular risk in early stages of life and to analyse whether there are variables associated with higher levels of CRP.…”
Section: Introductionmentioning
confidence: 99%